Respuesta :

Answer:

(x + 6)

(x - 7)

Step-by-step explanation:

To factor the polynomial in form [tex]x^{2} +bx+c[/tex] find two factors of C that have a sum of B

B = -1

C = -42

Factors of 42:

1, 2, 3, 6, 7, 14, 21, 42

6 and -7 multiply to -42 and add to -1

Write in factored form:

(x + 6)(x - 7)

Answer:

(x - 7)(x + 6)

Step-by-step explanation:

Given

x² - x - 42

Consider the factors of the constant term (- 42) which sum to give the coefficient of the x- term (- 1)

The factors are - 7 and + 6 , since

- 7 × 6 = - 42 and - 7 + 6 = - 1 , thus

x² - x - 42 = (x - 7)(x + 6)

ACCESS MORE